EXPLORING ETHICAL PERCEPTION OF TAX AVOIDANCE AMONG ACCOUNTING STUDENTS - Navael, Lovenka Diva; Wijaya, Suparna (Widya Mandala Surabaya Catholic University, 2024)
Research Purposes. This study examines the influence of Love of Money, Machiavellian, and Distrust to Fiscus, as well as Religiosity as a moderator on Ethical Perception of Tax Avoidance.Research Methods. This quantitative research collects primary data through online questionnaires. Respondents in this study included 117 accounting students from 26 universities in DKI Jakarta Province, who were selected using a purposive sampling technique. The data in this study were analyzed using the PLS-SEM method with the help of SmartPLS 4.0 software.Research Results and Findings. This study's results indicate that Machiavellian positively influences the Ethical Perception of Tax Avoidance. Meanwhile, the Ethical Perception of Tax Avoidance is not influenced by the Love of Money and the Distrust to Fiscus, and Religiosity also does not moderate it. The findings of this study are expected to enrich the literature related to the influence of Machiavellian on the Ethical Perception of Tax Avoidance and recommend to the Government and Universities to consider Machiavellian factors when formulating taxation and education policies.